The combined risk predictive power of frailty and hypoalbuminemia in free tissue flap reconstruction: a cohort study of 34,571 patients from the NSQIP database - Panayi, Adriana C.; Knoedler, Leonard; Matar, Dany Y.; Rühl, Jasmin; Friedrich, Sarah; Haug, Valentin; Palackic, Alen; Thomas, Benjamin; Kneser, Ulrich; Orgill, Dennis P.; Hundeshagen, Gabriel (Microsurgery, 2024)
Introduction Significant morbidity and mortality are hallmarks of the functional decline seen in physically frail patients. The modified frailty index 5 (mFI-5) represents a risk predictor score that has been validated as a comorbidity-based scale in surgery. Serum albumin levels of <3.5 g/dL (hypoalbuminemia) have also been implicated with poor postoperative outcomes. However, the association between these two parameters remains to be investigated. We aimed to elucidate the interdependence of preoperative albumin levels and frailty, as evaluated by the mFI-5 score, and its reliability to prognosticate postoperative results in free flap reconstruction (FFR). Methods We conducted a multicenter, retrospective cohort study and accessed the ACS National Surgical Quality Improvement Program (ACS-NSQIP) from 2008 to 2021. We identified all adult patients (≥18 years of age) who underwent a FFR. We extracted perioperative data and lab values including albumin. Multivariable linear and logistic regression analyses were performed to identify independent risk predictors. Main outcomes involved mortality, length of hospital stay, reoperation, medical and surgical complications, and discharge destination within the 30-day postoperative period. Results A total of 34,571 patients were included in the study, with an average age of 53.9 years (standard deviation [SD] 12.2) and an average body mass index (BMI) of 28.8 (SD 6.1). Of these patients, 7484 were male (21.6%), whereas 22,363 (64.7%) had no frailty (mFI = 0). Additionally, 9466 patients had a frailty score of 1 (27.4%), 2505 had a score of 2 (7.2%), 226 had a score of 3 (0.7%), and 11 had a score of 4 or higher (0.0%). Albumin levels were available for 16,250 patients (47.0%), and among them, 1334 (8.2%) had hypoalbuminemia. Regression analyses showed that higher mFI scores were independent predictors of any, surgical, and medical complications, as well as increased rates of reoperations, unplanned readmissions, and prolonged hospital stays. Hypoalbuminemia independently predicted any, surgical, and medical complications, and higher mortality, reoperation, and longer hospital stay. When both frailty and albumin levels (mFI-5 and albumin) were considered together, this combined assessment was found to be a more accurate predictor of all major outcomes (any, medical and surgical complications, mortality, and reoperation). Further, our analysis identified a weak negative correlation between serum albumin levels and mFI scores (Spearman R: −.1; p < .0001). Conclusion In conclusion, this cohort study highlights the association of hypoalbuminemia with adverse postoperative outcomes, including those not directly related to frailty. Simultaneously, higher mFI scores independently predicted outcomes not associated with hypoalbuminemia. Stemming from these findings, we recommend considering both serum albumin levels and frailty in patients receiving FFR. This perioperative algorithm may help provide more individualized planning including multidisciplinary care and pre and posthabilitation.
Erstmals veröffentlicht: 28 March 2024
Gesehen am 21.06.2024